Design of Religious-Based Extracurricular Activities in Shaping the Religious Character of Students in Madrasah Ibtidaiyah (EDUCARE: Journal of Primary Education, 2022)
Religious-based extracurricular activities are extracurricular activities that contain Islamic activities as the development of Islamic educational materials carried out outside school hours. This study aims to analyze the design of religious-based extra-curricular activities in shaping the religious character of students in Madrasah ibtidaiyah institutions. This study uses a qualitative approach. While the type of research using field research (field research). Data collection techniques using observation techniques, interviews, and documentation. While the data analysis using qualitative analysis model Miles and Huberman and Saldana models consisting of data condensation, data presentation and conclusion. While the validity of the data using triangulated sources and triangulation techniques. The results of this study showed that: 1) the application of religious-based extracurricular activities in shaping the religious character of students in MI Miftahul Huda, namely: a) Diba'iyah Activities, B) Tahlil activities, and c) Shalawat Al-Banjari. 2) factors supporting religious-based extracurricular activities in shaping the religious character of students in MI Miftahul Huda, namely: a) self-motivation of students, B) enthusiastic students follow the activities, c) participation of parents, and d) support from extracurricular coaches. 3) factors inhibiting religious-based extracurricular activities in shaping the religious character of students in MI Miftahul Huda, namely: a) lack of understanding of parents, b) students are easily affected, c) limited supervision of the school. Kegiatan ekstrakurikuler berbasis keagamaan merupakan kegiatan ekstrakurikuler yang memuat kegiatan-kegiatan islami sebagai pengembangan materi pendidikan islam yang dilaksanakan diluar jam sekolah. Kajian ini bertujuan untuk mengalisis tentang desain kegiatan ekstra kurikuler berbasis keagamaan dalam mebentuk karakter religius peserta didik di lembaga madrasah ibtidaiyah. Penelitian ini menggunakan pendekatan kualitatif. Sedangkan jenis penelitian menggunakan field research (penelitian lapangan). Tehnik pengumpulan data menggunakan teknik observasi, wawancara, dan dokumentasi. Sedangkan analisis data menggunakan model analisis kualitatif model Miles dan Huberman dan Saldana yang terdiri dari kondensasi data, penyajian data dan penarikan kesimpulan. Sedangkan keabsahan data menggunakan teriangulasi sumber dan triangulasi tehnik. Hasil penelitian ini menunjukan bahwa: 1) Penerapan kegiatan ekstrakurikuler berbasis keagamaan dalam membentuk karakter religius peserta didik di MI Miftahul Huda yaitu: a) Kegiatan Diba’iyah, b) Kegiatan Tahlil, dan c) Shalawat Al-Banjari. 2) Faktor pendukung kegiatan ektrakurikuler berbasis keagamaan dalam membentuk karakter religius peserta didik di MI Miftahul Huda, yaitu: a) motivasi diri peserta didik, b) antusias peserta didik mengikuti kegiatan, c) partisipasi orang tua, dan d) dukungan dari pembina ekstrakurikuler. 3) Faktor penghambat kegiatan ektrakurikuler berbasis keagamaan dalam membentuk karakter religius peserta didik di MI Miftahul Huda, yaitu: a) Minimnya pemahaman orang tua, b) Peserta didik mudah terpengaruh, c) Terbatasnya pengawasan dari pihak sekolah.